2014
DOI: 10.1007/s11307-013-0712-1
|View full text |Cite
|
Sign up to set email alerts
|

Pilot Study of a Novel 18F-labeled FSHR Probe for Tumor Imaging

Abstract: NOTA-MAL-FSH1 could be labeled rapidly and efficiently with (18)F using one step method. Favorable preclinical data suggest that (18)F-Al-NOTA-MAL-FSH1 may be a suitable radiotracer for the non-invasive visualization of FSHR positive tumor in vivo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
64
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 32 publications
(65 citation statements)
references
References 26 publications
1
64
0
Order By: Relevance
“…No-carrier-added [ 18 F]fluoride was obtained from an in-house cyclotron (HM67, Sumitomo Heavy Industries, Ltd.) Analytic and preparative high-performance liquid chromatography (HPLC) were performed according to the previous literatures. 30,31…”
Section: Methodsmentioning
confidence: 99%
“…No-carrier-added [ 18 F]fluoride was obtained from an in-house cyclotron (HM67, Sumitomo Heavy Industries, Ltd.) Analytic and preparative high-performance liquid chromatography (HPLC) were performed according to the previous literatures. 30,31…”
Section: Methodsmentioning
confidence: 99%
“…In the previous study, NOTA-MAL-FSH was designed and labeled with 18 F. 18 F-Al-NOTA-MAL-FSH was preliminarily evaluated in FSHR-positive PC3 prostate tumor by microPET image. Interrelated analyses concluded that the 18 F-Al-NOTA-MAL-FSH 33-53 had fast clearance rate, high specificity, excellent tissue penetration, and low immunogenicity, and may be a suitable radiotracer for the non-invasive visualization of FSHR positive tumor in vivo [24]. Based on these results, FSH 33-53 was used to connect Lytic peptide.…”
Section: Discussionmentioning
confidence: 99%
“…Preparation of NOTA-MAL-FSH 33-53 -Lytic FSH 33-53 -Lytic was conjugated with NOTA-MAL as described previously [24]. Briefly, a solution of 6 lmol FSH 33-53 -Lytic was mixed with 8 lmol NOTA-MAL in 0.2 M ammonium acetate solution.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Radiolabelled receptor-binding peptides have become important radiopharmaceuticals for diagnosis and therapy in tumor [57][58][59][60][61] .…”
Section: Radiolabeled Peptides For Pc Imagingmentioning
confidence: 99%